Spatial variability in factors that control the sinking flux of organic and inorganic particles in the Cariaco Basin: a vision from space. Issue 22 (17th November 2017) - Lorenzoni, L; Rueda, D; Montes, E; Varela, R; Rojas, J; Guzman, L; Astor, Y; Muller-Karger, F
ABSTRACT: The Cariaco Basin, located on the continental margin of the south-eastern Caribbean Sea, has been a site of extensive oceanographic research since the early 1950s. Here we examined the seasonal and spatial variability in satellite wind, sea surface temperature (SST), surface chlorophyll (CHL), and primary production (PP) within the Cariaco Basin (1994–2009). This variability has implications in modulating the vertical flux of particulate material to the bottom of the basin. While cross-shore Ekman Transport was positive (upwelling inducing) year-round, it showed 20–60% higher values (stronger upwelling) in the eastern sub-basin, compared to the western sub-basin 1.35–2.77 m 2 s −1 and 1.06–1.73 m 2 s −1, respectively; p  < 0.01). This translated into differences in CHL concentration and PP rates between the eastern and western Cariaco sub-basins. Long-term seasonal means of SST, CHL, and PP showed significant inter-basin differences ( p  < 0.01) between December and July; during that period the eastern basin was cooler (24.86 ± 1.03°C vs. 25.56 ± 0.80°C, p  < 0.01), with higher CHL (0.50 mg m −3 vs. 0.35 mg m −3 ; p  < 0.01) and PP (1763 ± 994 vs. 782 ± 129 mg C m −2 day −1, p  < 0.01) than the western sub-basin. The eastern Cariaco sub-basin had larger seasonal amplitude and variability in oceanographic characteristics than the western sub-basin, while the western sub-basin had slightly higher and more variable seasonal riverine run-off inputs. These differences have implications for the interpretation of the paleoclimate sediment record stored in different sectors of the Cariaco Basin.